Christian Responses to Islam in Nigeria - Akinade, A. author. aut Link
XV, 246 p.
Keywords: This book examines the various Christian responses to Islam in Nigeria. It is a study of the complex, interreligious relationships in Nigeria. Using a polymethodic approach, the book grapples with many narratives dealing with interreligious competition and cooperation in Nigeria.